Fast Growing Species for Meeting Rural and Industrial Needs of Punjab-present Status and Future Research Needs - Kapur, S. K.; Dogra, A. S. (Indian Forester, 1989)
In Punjab, the area under forests is extremely inadequate for meeting the requirement of the people for fuelwood and timber for individual needs The State Government has, therefore, encouraged farm and agro-forestry to increase wood production. Eucalyptus tereticornis has established itself as a timber species in the state. Poplar is another species which has found favour with the progressive farmers. The Punjab farmers have shown great zeal in raising tree crops. In order to sustain the interest in tree farming, it is necessary to set up wood-based industries which will in turn contribute significantly to the economic development of tbe state. At the same time, it is desirable to try indigenous species also so that undue dependence on tbe above species is avoided in tbe long term interest of environmental preservation. Research is therefore required in this direction urgently along with research on tbe production and utilization aspects of the established species.